Evaluation of [Cu]Cu-DOTA and [Cu]Cu-CB-TE2A Chelates for Targeted Positron Emission Tomography with an αβ-Specific Peptide - Sven H. Hausner; David L. Kukis; M. Karen J. Gagnon; Catherine E. Stanecki; Riccardo Ferdani; John F. Marshall; Carolyn J. Anderson; Julie L. Sutcliffe (Molecular Imaging)
Significant upregulation of the integrin α v β 6 has been described as a prognostic indicator in several cancers, making it an attractive target for tumor imaging. This study compares variants of a PEGylated α v β 6 -targeting peptide, bearing either an [>18F]fluorobenzoyl prosthetic group ([ 18 F]FBA-PEG-A20FMDV2) or different [ 64 Cu]copper chelators (DOTA-PEG-A20FMDV2, CB-TE2A-PEG-A20FMDV2). The compounds were evaluated in vitro by enzyme-linked immunosorbent assay (against the integrin α v β 6 and the closely related integrin α v β 6 ) and by cell labeling (α v β 6 -positive DX3puroβ6/α v β 6 -negative DX3puro) and in vivo using micro-positron emission tomography in a mouse model bearing paired DX3puroβ6/Dx3puro xenografts. In vitro, all three compounds showed excellent α v β 6 -specific binding (50% inhibitory concentration [IC 50 ](α v β 6 ) = 3 to g nmol/L; IC 50 (α v β 3 ) > 10 (μmol/L). In vivo, they displayed comparable, preferential uptake for the α v β 6 -expressmg xenograft over the α v β 6 -negative control (> 4:1 ratio at 4 hours postinjection). Whereas [ 64 Cu]Cu-DOTA-PEG-A20FMDV2 resulted in increased levels of radioactivity in the liver, [ 64 Cu]Cu-CB-TE2A-PEG-A20FMDV2 did not. Significantly, both 64 Cu-labeled tracers showed unexpectedly high and persistent levels of radioactivity in the kidneys (> 40% injected dose/g at 4 and 12 hours postinjection). The findings underscore the potential influence of the prosthetic group on targeted in vivo imaging of clinically relevant markers such as α v β 6 . Despite identical targeting peptide moiety and largely equal in vitro behavior, both 64 Cu-labeled tracers displayed inferior pharmacokinetics, making them in their present form less suitable candidates than the 18 F-labeled tracer for in vivo imaging of α v β 6